Neuropeptide W Exhibits Preventive and Therapeutic Effects on Acetic Acid-Induced Colitis via Modulation of the Cyclooxygenase Enzyme System - ARABACI TAMER, SEVİL; ERCAN, FERİHA; YEGEN, BERRAK (My University, 2023)
Background The novel peptide neuropeptide W (NPW) was originally shown to function in the control of feeding behavior and energy homeostasis. The aim of this study was to elucidate the putative preventive and therapeutic effects of NPW on colitis-associated oxidative injury and the underlying mechanisms for its action.Methods Sprague-Dawley rats in the acute colitis groups received NPW (0.5, 1 or 5 mu g/kg/day) injections prior to induction of colitis with acetic acid, while the chronic colitis groups were treated after the induction of colitis. In both acute and chronic colitis (CC) groups, treatments were continued for 5 days and the rats were decapitated at the 24th hour of the last injections and colon tissues were collected for assessments.Results NPW pretreatment given for 5 days before colitis induction, as well as treating rats with NPW during the 5-day course of CC, abolished colonic lipid peroxidation. NPW treatment prevented colitis-induced reduction in blood flow, diminished neutrophil infiltration, and pro-inflammatory cytokine responses. NPW pretreatment only at the higher dose reduced colonic edema and microscopic score and preserved colonic glutathione stores. Elevations in cyclooxygenase (COX) enzyme activity and COX-1 protein level during the acute phase of colitis as well as reduction in COX-2 were all reversed with NPW pretreatment. In contrast, NPW treatment was effective in reducing the elevated COX-2 concentration during the chronic phase.Conclusions NPW alleviates acetic acid-induced oxidative colonic injury in rats through the upregulation of colonic blood flow as well as the inhibition of COX-2 protein expression and pro-inflammatory cytokine production.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Gastroenteroloji-(Hepatoloji); Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Gastroenterology and Hepatology; Health Sciences; GASTROENTEROLOJİ VE HEPATOLOJİ; Klinik Tıp; Klinik Tıp (MED); GASTROENTEROLOGY & HEPATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Hepatoloji; Gastroenteroloji; Hepatology; Gastroenterology; Neuropeptide W; Ulcerative colitis; Oxidative injury; Inflammation; Cyclooxygenases; INFLAMMATORY-BOWEL-DISEASE; NITRIC-OXIDE SYNTHASE; ULCERATIVE-COLITIS; CROHNS-DISEASE; BLOOD-FLOW; RATS; EXPRESSION; STRESS; CELLS; PATHOGENESIS